Enhancing Lecturer Work Productivity Through Organizational Culture, Servant Leadership, Interpersonal Communication, And Achievement Motivation At Pesantren-Based Islamic Higher Education Institutions - Marzuki, Marzuki; Rubini, Bibin; Setyaningsih, Sri (Al Irsyad: Jurnal Studi Islam, 2026)
The productivity of lecturers at pesantren-based Islamic Higher Education Institutions remains relatively low due to organizational culture, kyai leadership, suboptimal interpersonal communication, and varying levels of achievement motivation across individuals and work units. This condition requires a comprehensive examination of internal and external factors that shape academic performance. The study aims to determine the influence of organizational culture, servant leadership, and interpersonal communication on lecturer productivity through achievement motivation as an intervening variable. A quantitative survey approach was employed involving 105 lecturers selected through proportional random sampling, with data analyzed using path analysis and the Sobel test to examine both direct and indirect effects. The findings indicate that servant leadership has a significant direct effect on lecturer productivity (beta = 0.135), while achievement motivation also shows a significant effect (beta = 0.237). In addition, organizational culture, servant leadership, and interpersonal communication significantly influence productivity indirectly through achievement motivation. SITOREM analysis identifies areas requiring improvement, including scientific publications, community service, and time management, while teaching performance and technology utilization must be maintained and strengthened. These results highlight the importance of integrating organizational, leadership, communication, and motivational factors sustainably. Overall, lecturer productivity is shaped by both direct and indirect effects mediated by achievement motivation. The study provides a strategic foundation for pesantren-based Islamic Higher Education Institutions managers to enhance lecturer productivity through strengthening organizational culture, leadership practices, communication quality, and achievement motivation development.